Individual shark profiling: An innovative and environmentally responsible approach for selectively managing human fatalities. Issue 2 (11th November 2018) - Clua, Eric E. G.; Linnell, John D. C.
Abstract: Most shark‐induced human fatalities are followed by widespread and unselective culling campaigns that have limited effectiveness and may have high ecological costs for threatened species. The blanket culling strategy implicitly assumes that incident risk is directly correlated with shark density, an assumption that has yet to be demonstrated. We present the alternative hypothesis that incidents are more likely to be caused by behavioral variability among individual sharks than due to shark density. Throughout their ontogenetic development, large species of sharks opportunistically establish a diet that is rarely, if ever, inclusive of humans as a food source. We propose that, some animals with specific behaviors (including boldness) may potentially pose a higher risk than conspecifics. Under this scenario, the risk of a shark attack in a given area would relate to the presence of a limited number of high‐risk individuals rather than shark density. In terms of management of human fatalities, such a hypothesis would favor abandoning general culling campaigns and replacing them with approaches that profile and selectively remove the potential problem individuals, as is done in the terrestrial realm when managing predators that attack humans or livestock.